Trends and Future Directions in Sustainable Development - Sooksiri Wichaisri (2018)
Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment This study aims to explore research and to identify research clusters on sustainable development by using bibliometric analysis. The sustainable development field is examined using the selected research articles. A co-citation unit is used to analyze the relationship between cited documents, and then science mapping is used to identify clusters in this relationship. The results show that there are four main distinct clusters, of which the most important concerns sustainable supply chains and logistics management. This cluster is then classified into five bunches of knowledge sources. These bunches illustrate the need for a trend in sustainability issues that includes a social dimension to balance economic and environmental dimensions for long-term development. There are logistics management and lean concepts that can be applied to sustainable development to move toward business sustainability. The future direction of sustainable business concerns economic values, environmental policy and stakeholder engagement for business opportunities. The contribution of this article is to identify trends in sustainable development by means of bibliometric analysis, to develop research in the future. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment.